2015
DOI: 10.1128/cvi.00001-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Commercial Type 1 Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) Modified Live Vaccines against Heterologous Type 1 and Type 2 PRRSV Challenge in Growing Pigs

Abstract: The objective of the present study was to compare the efficacy of two commercial type 1 porcine reproductive and respiratory syndrome virus (PRRSV) modified live vaccines against heterologous type 1 and type 2 PRRSV challenge in growing pigs. Vaccination with a type 1 PRRSV vaccine reduced the level of viremia after type 1 PRRSV challenge but did not reduce the level of viremia after the type 2 PRRSV challenge in pigs. Increased levels of interleukin-10 (IL-10) stimulated by type 2 PRRSV coincided with the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 28 publications
4
49
1
Order By: Relevance
“…Some studies have found similar incomplete effect of vaccination following challenge of PRRSV-1 vaccinated pigs with heterologous PRRSV-1 strains [17,26], while others have found significant reduction in viremia following PRRSV-1 vaccination in a quasi-natural experimental model [27] and clinical protection in the field despite the field strain was only 85% identical to the vaccine strain in ORF 5 [19]. In the present study, vaccination against PRRSV-1 did not protect against challenge with Type 2 virus which are in accordance with the majority of previous studies [26,[28][29][30]. The challenge in the present study was performed approximately two months after vaccination which is later than in most vaccine trials.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have found similar incomplete effect of vaccination following challenge of PRRSV-1 vaccinated pigs with heterologous PRRSV-1 strains [17,26], while others have found significant reduction in viremia following PRRSV-1 vaccination in a quasi-natural experimental model [27] and clinical protection in the field despite the field strain was only 85% identical to the vaccine strain in ORF 5 [19]. In the present study, vaccination against PRRSV-1 did not protect against challenge with Type 2 virus which are in accordance with the majority of previous studies [26,[28][29][30]. The challenge in the present study was performed approximately two months after vaccination which is later than in most vaccine trials.…”
Section: Discussionsupporting
confidence: 92%
“…The latter studies investigated cross-protection of PRRSV vaccine (Park and others 2014a, 2015, Kim and others 2015). Pigs immunised with type 1 PRRSV vaccine had reduced levels of type 1 PRRSV viraemia when challenged with the same type 1 PRRSV but showed no effect on the levels of type 2 PRRSV viraemia when challenged with the same type 2 PRRSV (Kim and others 2015). In contrast, pigs immunised with the same type 2 PRRSV vaccine exhibited reduced levels of type 1 and type 2 PRRSV viraemia when challenged with the same type 1 and type 2 PRRSV (Park and others 2014a, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR for the vaccine virus was also performed to quantify PRRSV genomic cDNA copy (Park and others 2014a, Kim and others 2015). …”
Section: Methodsmentioning
confidence: 99%
“…For PRRSV‐2, the forward and reverse primers were 5′‐TGGCCAGTCAGTCAATCAAC‐3′ and 5′‐AATCGATTGCAAGCAGAGGGAA‐3′, respectively (Wasilk et al., ). For UNISTRAIN vaccine virus, the forward and reverse primers were 5′‐ GTTGCCCAGCCATTTTGAC‐3′ and 5′‐CACGCTGCTGAGTACATACC‐3′, respectively (Kim et al., ). RT‐PCR for PRRSV was used to quantify PRRSV genomic cDNA copy numbers using RNA extracted from serum samples as previously described (Park, Seo, Han, Kang, & Chae, ; Wasilk et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…This PRRSV‐1 MLV vaccine can protect against both PRRSV types based on the manufacturer's claims (http://www.hipra.com). However, this claim has been somewhat controversial as experimental data about cross‐protection of this PRRSV‐1 MLV vaccine against respiratory disease caused by PRRSV‐2 in growing pigs do not support this claim (Kim et al., ). Furthermore, vaccine efficacy against PRRSV‐1‐ or PRRSV‐2‐caused reproductive failure in gilts or sows has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%